Satellite Unknowns in Irreducible Differential Systems - Panferov, A. A. (Programming and computer software, 2018)
In this paper, the concept of satellite unknowns in differential systems with selected unknowns is considered in the context of irreducible systems. It is proved that any unselected unknown in an irreducible differential system is linearly satellite for any nonempty set of selected unknowns. An algorithm for factorization of differential systems is proposed that is not always applicable but executable in polynomial time. Cases where the algorithm cannot be applied are also recognized in polynomial time.